(3fhQ GdCHUGQ GdefJRY ef cJGH GdEfJUGQs - (3GdMGaX jhSa Hf CMeO Hf eMeO GdRjOis ((3eMeO Hf jhSa Hf CMeO GdQjGMi s)
(3ChdgG (B:s
(3HMeOc Gddge CaJJM GdebGd hHTcQc fSJYjf Ydi UdGM GdCMhGd , hHYahc hZaQGfc Hg CfhW GdCeGd s
(3BNQgG (B:s
(3acja EPG CXgQ GdcQGgI Hbdjg hdSGfg hGdMeO ddg hdi GdMeO hGdGaVGd agPG JeGe GdefJRY GdeHGQc s
(3HgG Jedc HGSe GdMSf Hf efUhQ Hf GdeOes
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , CQVg , JQeje s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds